2004
DOI: 10.1002/chin.200412178
|View full text |Cite
|
Sign up to set email alerts
|

Three Diterpenoids (Excoecarins V1—V3) and a Flavanone Glycoside from the Fresh Stem of Excoecaria agallocha.

Abstract: Excoecaria agallocha LINN. (family Euphorbiaceae) is distributed on seashores and edge-mangroves throughout tropical Africa, Asia, and northwest Australia. 1) The Excoecaria genus is well known to contain skin irritants, called irritant Excoecaria factors. In traditional Thai medicine, the bark and wood of the plant is used to treat flatulence. 2,3) In Sri Lanka, the smoke of the burning wood is used in the treatment of leprosy, and the root, when pounded with ginger, as an embrocation for swollen hands and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Clinical trials carried out on this plant showed its potential as anti-HIV, anticancer, antibacterial and antiviral agent (Peter et al, 1999). Previous phytochemical studies on E. agallocha revealed the presence of diterpenoids (ISI database, 2008;Ji-Dong et al, 2007;Li et al, 2007;Wang et al, 2006Kang et al, 2005), triterpenoids (Zou et al, 2006), fl avonoid (Konishi et al, 2003) and phorbole esters (Ericson et al, 1995). As part of our continuing phytochemical and bioactivity studies on Bangladeshi medicinal plants and also in other parts of the world (Alam et al, 2008a,b;Ali et al, 2008;Datta et al, 2007Datta et al, , 2004Saha et al, 2007;Uddin et al, 2007aUddin et al, -c, 2006aUddin et al, ,b, 2005Uddin et al, , 2004Rouf et al, 2006;Haque et al, 2004;Rahman et al, 2004;Delazar et al, 2006;Shoeb et al, 2007;Auzi et al, 2007;Zamani et al, 2007;Razavi et al, 2008), we now report on the neuropharmacological and antibacterial activities, and acute toxicty of the ethanol extract of the bark of E. agallocha in laboratory rodents as well as brine shrimp toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials carried out on this plant showed its potential as anti-HIV, anticancer, antibacterial and antiviral agent (Peter et al, 1999). Previous phytochemical studies on E. agallocha revealed the presence of diterpenoids (ISI database, 2008;Ji-Dong et al, 2007;Li et al, 2007;Wang et al, 2006Kang et al, 2005), triterpenoids (Zou et al, 2006), fl avonoid (Konishi et al, 2003) and phorbole esters (Ericson et al, 1995). As part of our continuing phytochemical and bioactivity studies on Bangladeshi medicinal plants and also in other parts of the world (Alam et al, 2008a,b;Ali et al, 2008;Datta et al, 2007Datta et al, , 2004Saha et al, 2007;Uddin et al, 2007aUddin et al, -c, 2006aUddin et al, ,b, 2005Uddin et al, , 2004Rouf et al, 2006;Haque et al, 2004;Rahman et al, 2004;Delazar et al, 2006;Shoeb et al, 2007;Auzi et al, 2007;Zamani et al, 2007;Razavi et al, 2008), we now report on the neuropharmacological and antibacterial activities, and acute toxicty of the ethanol extract of the bark of E. agallocha in laboratory rodents as well as brine shrimp toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical screening shows the presence phorbol ester, flavanone, glycoside, various di-and triterpenoids, 15 dichloromethane, lignin, pentosan, α cellulose saponin, tannins, phenols, volatile oils. 16,17,18 Pharmacological investigation of the various extracts of the plant shows antibacterial, antioxidant, anti-diabetic, antibacterial, antinociceptive effects .it is also reported it has some impact on the treatment of mosquito borne diseases and pandemic diseases.…”
Section: Excoecaria Agallochamentioning
confidence: 99%
“…They are formed from the oligomeric structures of phloroglucinol (1,3,5trihydroxybenzene) (Parys et al, 2007). Also, some flavanone glycosides have been found even in fresh water algae (Konishi et al, 2003).…”
Section: Antioxidantsmentioning
confidence: 99%